Between similarity and difference: network dynamics of the hippocampal- parahippocampal circuitry in pattern separation of male Wistar rats - Araujo, Ana Paula de Castro; Parente, Jeanderson Soares; Coutinho, Sofia Lucena de Oliveira; Castelo-Branco, Rochele; Meurer, Ywlliane S. R.; Barbosa, Flávio Freitas (Frontiers in Cellular Neuroscience, 2025)
IntroductionStudies indicate that pattern separation for spatial and object information involves structures of the temporal cortex (lateral entorhinal and perirhinal cortices) and hippocampus (dentate gyrus and CA3), which are particularly sensitive to aging. However, little is known about how the hippocampal network, the anteroposterior axis of these regions, and the excitatory-inhibitory circuit contribute to the recognition and separation of object patterns.MethodsThis study investigated the expression of c-Fos and PV along the anteroposterior axis of the hippocampus in a multi-trial task to assess the recognition of novel objects and recognition of novel objects with different levels of similarity. Five groups of animals performed tasks with different similarity demands (NOR, DIST, 25, 50, 75%).ResultsThe data showed that conditions of greater similarity led to increased c-Fos expression in CA3c and Hilus in the rostral hippocampus. Graph analysis revealed that hippocampal networks became more densely interconnected and efficient as object similarity increased. Furthermore, different patterns of cluster organization emerged depending on task demands. Besides, the granule cell layer along the dorsoventral axis exhibited greater activation of inhibitory neurons (PV+/c-Fos+) under conditions of higher similarity. Differential inhibitory/excitatory control of the DG-CA3 microcircuit network is seen across conditions. Modeling the DG layers revealed robust control of GCs through direct and indirect effects of interneurons present in the hilus and granule layer. Bidirectional direct and indirect effects of MCs on GCs were observed.DiscussionThese results contribute to our understanding of how brain networks and DG excitatory/inhibitory microcircuits are jointly engaged in object recognition memory and disambiguation of overlapping inputs.